Tuberculosis of Zygapophyseal Joint: A Report of 3 Cases Observed in the University Hospital Center of Cocody in Abidjan (CAte dIvoire) (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: bone and joint tuberculosis - zygapophyseal arthritis #x2013; CT scan-magnetic resonance imaging - abidjan